Penerapan Strategi Index Card Match Berbantu Media Power Point untuk Meningkatkan Penguasaan Kosakata Bahasa Arab - Yeni Lailatul Wahidah; Zulhannan Zulhannan; Noviyanti Noviyanti (PTK: Jurnal Tindakan Kelas, 2024)
The purpose of this study was to determine whether by applying the index card match strategy strategy assisted by power point media can improve the mastery of Arabic vocabulary of students in class IV MI Al Juharotunnaqiyah South Lampung. This research using Classroom Action Research (PTK) with Kemmis and . Mc Teggart model which was carried out in two cycles. Cycles. Data collection techniques were observation, documentation, interviews and learning outcome tests. multiple choice and description. The results showed an increase in student learning outcomes after applying index card match strategy assisted by power point media in the pre-cycle. pre-cycle, namely students who completed 7 (40%) and those who did not complete 14 (60%). 14 (60%). In cycle II there was an increase of 18 (73%) and those who did not complete 5 (21%). In cycle II there was cycle II there was an increase of 20 (87%) students who were complete and 3 (13%) who were not complete. 3(13%). So that there was an increase of 61%. Based on the results of research and data analysis, it can be concluded that the application of the index card match strategy assisted by power point media can improve students' mastery of Arabic vocabulary in Class IV MI Al Juharotunnaqiyah South Lampung.